STUDENTS’ POLITENESS STRATEGIES IN TEXTING (A) LECTURER - Rahmi, Gita (Journal of Language and Literature, 2020)
Being polite linguistically is one issue that is faced by the students right now. The way they text their lecturer reflects their politeness. This research aimed at finding out the students’ politeness in texting their lecturer which in this research was their final project advisor. The research was conducted in qualitative and the data were taken from the students’ texts received by the lecturer. In this research, the text was collected from WhatsApp application. There were 37 messages collected and analyzed. Most of them were texts from the students to their advisor. The data were analyzed by using theory from Brown and Levinson (1987) as the guidance. The result showed that most of the students started their text with the greeting but mostly in informal way. Then, some FTAs were also found in the students’ texts which were possibly done by the students by coincidence. They seemed to be unaware to destroy the hearer’s face (in this case the lecturer). The most used politeness strategy by students in texting the lecturer was bald on-record (18 messages) and the least used was off-record (one message). Then, a few texts showed that some students applied negative politeness strategies where they considered status, time and apology for interrupting the lecturers. Positive politeness was also found in the students’ texts to the lecturer. This research is expected to inspire other researchers to conduct more comprehensive research related to the students’ politeness in texting their lecturers. This research did not only offer an analysis of students’ politeness to the lecturers which has been commonly done, it showed the politeness of the students to their advisor. This research focused more on investigating the students’ politeness in texting their advisor through WhatsApp Text.